Refining the Frommelt Attitude Toward the Care of the Dying Scale (FATCOD–B) for medical students: A confirmatory factor analysis and Rasch validation study. Issue 1 (15th May 2017) - Loera, Barbara; Molinengo, Giorgia; Miniotti, Marco; Leombruni, Paolo
ABSTRACT: Objective: Given the increasing number of patients requiring palliative care and the need for more professionals who are able to provide care for the dying comfortably, assessment of medical attitudes toward end-of-life care is becoming a key aspect of medical education. The present study aimed to establish whether the Frommelt Attitude Toward the Care Of the Dying, Form B (FATCOD–B) meets current psychometric standards of validity for an assessment tool in medical education. Method: The participants were 200 undergraduate medical students. Since in a previous study the FATCOD–B was found to have a weak structure due to poor item validity, a refined version was proposed and tested in the present study. Confirmatory factor analysis and the Rasch model were employed to assess its dimensionality and psychometric properties. Results: The construct measured by the FATCOD–B continues to be misspecified. The tool has a two-dimensional structure. The first is well-structured and demonstrates appreciable measurement and discriminant capabilities. The second has low validity because its measurement capabilities are based on weakly correlated items. Significance of results: Our results suggest that the FATCOD–B measures a two-dimensional construct and that only its first dimension is a robust measurement tool for use in medical education to evaluate undergraduates' attitudes about caring for the dying.